HYDROLYSIS OF WHEAT STRAW UNDER ALKALI CONDITIONS - & Shakir, AL-Rubaia’ay (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Ground wheat straw autoclaved and non-autoclaved (l0g) was treated with 6, 8 and 10%  sodium hydroxide of 1:10, 1:15 and1:20 mixing ratio for 1, 2 and 3hrs as reaction time. Results revealed a maximum value (18.79 %) of xylose were found in hydrolysate when autoclaved wheat straw was treated with 8% NaOH for 2hrs , whereas  the lowest value was (13.52) % when the non autoclaved wheat straw (  6% sodium hydroxide concentration , 1h reaction time  and 1:10 solid: liquid ) used. Also, results indicated that  the highest level of furfural (0.34) % was observed when 10 % sodium hydroxide  solution  over 3 hrs incubation was used. while, the lowest level (0.11)%  was observed when 6% sodium hydroxide  after 1hr reaction was used, demonstrating that the reaction time and alkaline concentration has very significant role in furfural formation .